The Human Bone Marrow Is Host to the DNAs of Several Viruses - Toppinen, Mari; Sajantila, Antti; Pratas, Diogo; Hedman, Klaus; Perdomo, Maria F. (Frontiers in Cellular and Infection Microbiology, 2021)
The long-term impact of viruses residing in the human bone marrow (BM) remains unexplored. However, chronic inflammatory processes driven by single or multiple viruses could significantly alter hematopoiesis and immune function. We performed a systematic analysis of the DNAs of 38 viruses persisting in the BM. We detected, by quantitative PCRs and next-generation sequencing, viral DNA in 88.9 % of the samples, up to five viruses in one individual. Included were, among others, several herpesviruses, hepatitis B virus, Merkel cell polyomavirus and, unprecedentedly, human papillomavirus 31. Given the reactivation and/or oncogenic potential of these viruses, their repercussion on hematopoietic and malignant disorders calls for careful examination. Furthermore, the implications of persistent infections on the engraftment, regenerative capacity, and outcomes of bone marrow transplantation deserve in-depth evaluation.